MENJEMPUT SENYUMAN : DUKUNGAN PSIKOSOSIAL ANAK-ANAK KORBAN BENCANA TSUNAMI DI ANYER - Sagita, Dony Darma; Nur Fairuz, Shafna Utami (Universitas Muhammadiyah Tapanuli Selatan, 2019)
The tsunami disaster that struck the Anyer region, Banten at the end of 2018 had a physical and psychological impact on the community, especially on vulnerable communities, namely children, women and the elderly. The purpose of this service is to provide support and assistance to children who are victims in reducing stress and trauma caused by disasters so that they can smile again as before. In carrying out my activities in collaboration with Inter Club Indonesia (ICI) volunteers and Muhammadiyah Disaster Management Center (MDMC). Activities carried out include socio drama, fairy tales, coloring and counseling services. As a result of dedication found in the enthusiasm and changes in the children who experience traumatic post-disaster, the children participate in activities with enthusiasm and active. Because of the magnitude of the benefits and impacts of this activity it is necessary to proceed with more thorough procedures and preparation in the future. So that the psychological wounds of children and adolescents can be alleviated and the smiles of children can return them on their faces.